UJI AKTIVITAS ANTIBAKTERI PASTA GIGI EKSTRAK BIJI PINANG (Areca catechu L.) TERHADAP Streptococcus mutans DAN Staphylococcus aureus - Nur Afni; Nasrah Said; Yuliet Yuliet (Universitas Tadulako, 2015)
Betel nut (Areca catechu L.) is a natural material that has antibacterial activity content against Streptococcus mutans and Staphylococcus aureus. Under these conditions, betel nuts were formulated in a toothpaste that has antibacterial activity.This study aims to determine the antibacterial activity of betel nut extract in toothpaste with various concentrations of 1.5%, 3% and 4.5% and to determine the effective concentration of betel nut extract in toothpaste that meets the physical quality of chemical and antibacterial activity against Streptococcus mutans and Staphylococcus aureus. The research design used was a completely randomized design (CRD). Extraction was done by maceration using ethanol 96%. Viscous extract obtained in the preparation of toothpaste formulated with a concentrations of 1.5%, 3% and 4.5%. All tested formula toothpaste physical quality of chemical (organoleptic, homogeneity, pH, viscosity and foaming) and antibacterial activity. The data obtained in the physical quality of chemical testing were analyzed descriptively and antibacterial activity data were statistically analyzed using One Way ANOVA at 95% confidence level, followed by Duncan test using SPSS. The test results show that the antibacterial toothpaste with betel nut extract concentrations of 1.5%, 3% and 4.5% show antibacterial activity against Streptococcus mutans and Staphylococcus aureus. Formula toothpaste as an antibacterial effective against bacteria test is F3 with betel nut extract concentration of 4.5%, which result in the diameter of the inhibition of Streptococcus mutans by 11.37 mm and 20.03 mm for Staphylococcus aureus. The test results show all the physical quality of chemical toothpaste betel nut extracts meet the physical quality of chemical toothpaste